Optical determination of oxygen mass transfer in a helically-coiled pipe compared to a straight horizontal tube. (23rd November 2018) - Kováts, P.; Pohl, D.; Thévenin, D.; Zähringer, K.
Highlights: Measurement of mass transfer coefficients in a helical pipe. Locally resolved measurement through colour reaction with resazurin. Comparison with straight horizontal tube shows the advantages of the helix. First two to three turns have about one order of magnitude higher volumetric mass transfer coefficients. Abstract: The gas-liquid mass transfer of oxygen has been examined experimentally in a helically-coiled pipe using an optical colorimetric method. Two tracer redox-reactions have been used for this purpose: (i) methylene blue and (ii) resazurin. The gas hold-up has been varied from 0.1 to 0.6, and liquid flow rate from 0.37 to 0.68 l/min, both leading to plug-flow conditions in the helix for all parameter combinations. A progress variable has been defined to measure the advancement of the reaction and thus, oxygen transfer to the liquid. The resazurin reaction turned out to be more appropriate for mass transfer studies, due to the bigger time constant difference of oxidation and reduction. Therefore, it can be adapted more easily to the specific conditions of the set-up. It also possesses more intense colours and higher fluorescence intensity, which might be useful for other mass transfer studies. As expected, the oxygen mass transfer increases with gas hold up, but liquid flow rate has little influence. A comparison with a horizontal tube of the same diameter shows the drastically increased mass transfer in the helix, due to better radial mixing and different flow pattern. Depending on the experimental conditions, oxygen concentration in the helix was up to twice that of the horizontal tube. This can be explained by the much higher liquid side mass transfer velocity, which is determined in this study from the experimental kl a -values and specific bubble surface per turn of the helix. For this purpose, bubble dimensions and gas-liquid cell volumes have been determined from the experimental images. The paper thus presents a locally resolved characterization of gas-liquid mass transfer in a helically coiled reactor. The high mass transfer especially during the first turns of the helix shows its advantages compared to a straight tube.